USING TEAM WORD WEBBING TO TEACH READING COMPREHENSION ON NEWS ITEM TEXT FOR SENIOR HIGH SCHOOL STUDENTS - Mulia Putri; Jufri Jufri (Universitas Negeri Padang, 2018)
This paper is conducted based on phenomena faced by the writer in her teaching practice. As demanded by K-13 the objective of teaching reading is to develop students reading skill, so they can read and comprehend the text appropriately. At senior high school, one of texts that should be mastered by students is News Items. Based on the writer’ observations there are so many students who have difficulty in reading comprehension the text. It is caused of several factor influences the students’ reading comprehensions such as monotone reading activity, learning environment and strategy or technique used by the teacher is not interesting by the students. Therefore it is needed a new reading strategy applied to solve this problem for the students to comprehend the text through Team Word Webbing. Team Word Webbing is a kind of semantic mapping or clustering strategy used to make the students actively participate in team or group. This paper is aimed at discussing how to use Team Word Webbing in teaching reading comprehension on news item text for Senior High School Student. By applying this strategy, the writer hopes that this paper will help the students to be motivated and interested in reading process.